Molecular Basis of Triple Negative Breast Cancer and Implications for Therapy. (2nd November 2011) - Peddi, Parvin F.; Ellis, Matthew J.; Ma, Cynthia
Abstract : Triple negative breast cancer is an aggressive form of breast cancer with limited treatment options and is without proven targeted therapy. Understanding the molecular basis of triple negative breast cancer is crucial for effective new drug development. Recent genomewide gene expression and DNA sequencing studies indicate that this cancer type is composed of a molecularly heterogeneous group of diseases that carry multiple somatic mutations and genomic structural changes. These findings have implications for therapeutic target identification and the design of future clinical trials for this aggressive group of breast cancer.